Tradition and ephemerality : suburban voices in Dermot Bolger and Roddy Doyle - Gerber, Astrid (Trinity College (Dublin, Ireland). School of English, 2002)
This thesis is a work of literary critique. It attempts to explore the significance of the concepts of tradition and ephemerality within the work of Dermot Bolger and Roddy Doyle. This is done not only on the level of content, where literary texts undergo close reading, interpretation and explication, but also on the level of form. Consideration of narrative form leads the critic to a broader understanding of the effects of the literary text on the reader as well as to the debate as to whether that form complements or contradicts the intended meaning of the novel. Examination of tradition and ephemerality leads also, however, inexorably to an investigation of how the literary critic should react to such texts which throw up questions about the way literature endures and interacts with its environment. Dermot Bolger and Roddy Doyle are the most widely read of the new generation of Dublin writers, but the primary concern of their work up to the mid 1990s was the need to give a voice to a suburban community which had barely been considered in Irish literature. Bolger focuses on the state of 'limbo' in which the suburb-dwellers find themselves and describes the resulting attempt to fix upon a heritage and tradition so that they can finally feel 'at home'. However, since the suburban community not only has to come to terms with being marginalized within Ireland, Bolger's characters discover that this is reflected also in the relation between Ireland and Europe.
Keywords: Language and Literature. English, Ph.D.; Ph.D. Trinity College Dublin